HISTORY OF STUDYING OF REPRESENTATIVES OF SORT PLANTAGO L. IN THE NORTH CAUCASUS - R. S. Erzhapova; T. S. Khasanov; Z. N. Amalova (Юг России: экология, развитие, 2014)
The first monography considering systematization of family Plantaginaceae, work «Esquise de l’historie naturelle des Plantaginees» is. The morphology generative and vegetative bodies of plantains is widely enough considered in the monography «Die Plantagi-neen in Bezug auf die naturhistorische Spezies». In modern researches of systematization of plantains of A.B. Shipunov allocates nomenclature specifications of names of set of kinds, and also intraspecific and intrapatrimonial groups of plantains; researches of systematization of separate groups; research of flora of various regions and the description of new kinds. Sources of formation of the first scientific collections on flora of caucasus had I.Gildenshtedt's Petersburg academicians (Gűldenstadt, 1787, 1791), Of this year Gmelin (Gmelin, 1784), P.S.Palas (Pallas, 1789-1790) (Shcherbakova, 1979) and I.P.Falk (1773).